2022
DOI: 10.1038/s41598-022-08672-5
|View full text |Cite
|
Sign up to set email alerts
|

Dissipated electroosmotic EMHD hybrid nanofluid flow through the micro-channel

Abstract: The main objective of the present study is to explore the effects of electromagnetohydrodynamics electroosmotic flow of hybrid nanofluid through circular cylindrical microchannels. An analysis of hybrid nanofluid consisting of four different nanomaterials i.e., single and multiwall carbon nanotubes, silver, and copper is carried out. Yamada–Ota model is employed for the single and multi wall carbon nanotubes, whereas, Xue model is used for the Silver and Copper hybrid nanofluid for specifying the thermal condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…An enhancement in thermal heat transfer of 33.67% was observed for the ternary hybrid nanofluid flow when compared with the unitary nanofluid flow. Recent studies featuring hybrid nanofluid flow in various scenarios may be observed in [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…An enhancement in thermal heat transfer of 33.67% was observed for the ternary hybrid nanofluid flow when compared with the unitary nanofluid flow. Recent studies featuring hybrid nanofluid flow in various scenarios may be observed in [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioconvection steady nanofluid flow through the stretching sheet is taken in the existence of electric and magnetic force . Electroosmotic dissipation is observed for the electromagnetohydrodynamic hybrid nanofluid flow that past a micro-channel . Wettability and interfacial tension have been studied taking multi-nanofluids named hybrid-nanofluid under the influence of electromagnetic force .…”
Section: Introductionmentioning
confidence: 99%
“… 46 Electroosmotic dissipation is observed for the electromagnetohydrodynamic hybrid nanofluid flow that past a micro-channel. 47 Wettability and interfacial tension have been studied taking multi-nanofluids named hybrid-nanofluid under the influence of electromagnetic force. 48 Another beneficial research about MHD exists in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Jamei et al [19] estimated the thickness of HNFs for current dynamism application. Bilal et al [20] used the degenerate electroosmotic EMHD HNFs over the micro-passage.…”
Section: Introductionmentioning
confidence: 99%